Clinical Features and the Use of Three-Dimensional Imaging for Unilateral Lambdoid Synostosis. Issue 1 (17th September 2021) - Diab, Jason; Fowler, Adam; Gates, Robert; Marucci, Damian D.
Abstract : Supplemental Digital Content is available in the text Abstract : Introduction: True isolated lambdoid craniosynostosis is rare. It requires corrective surgery to prevent intracranial pressure and aesthetic stigma by significant dyscrania. We summarize our case series for lambdoid craniosynostosis outlining the pathophysiology, clinical findings and surgical approaches and outcomes. Methodology: A retrospective analysis of our data from 2010 to 2020 summarized our cases of true lambdoid synostosis. We have used the medical notes and the radiological findings from computed tomography scans to summarize a case series of isolated lambdoid synostosis. Results: Our case series demonstrated 7 patients with true isolated lambdoid craniosynostosis. In most cases surgical intervention in the form of posterior cranial vault remodeling utilizing a bandeau, based on occipital advancement techniques, has demonstrated the most consistently favorable aesthetic outcome. Conclusions: Surgical referral to a craniofacial center should be sought early in difficult to diagnose cases. Although rare, surgical intervention is indicated to correct potentially increased intracranial pressure and to ameliorate cranial dyscrania.